(untitled) (CIPEEX, 2025)
This study aims to analyze how ageism affects users of the digital environments of financial institutionsin the financial institutions in the São Patrício Valley, a region in the state of Goiás. The research pointsto the technological in the financial system, along with the obstacles faced by the elderly in accessingthese technologies. Age is one of the characteristics that stands out when analyzing people’s profiles.Ageism occurs when age is used to categorize and divide people, causing conflicts betweengenerations.between generations, with discrimination and exclusion as its characteristic, associating oldage with a lower old age as a phase of lower income, and ageism is generally associated with olderpeople. These obstacles can aggravate digital exclusion among the elderly. In this way, the work willuse an exploratory approach to analyze the theme, with field research in the São Patrício Valley. In theSão Patrício Valley to analyze users’ perceptions of the relationship between the use of technology inbetween the use of technology in financial institutions and age. The methodology includes of anelectronic questionnaire, considering the criterion of simple random sampling and the statistical analysisof the data collected, with the aim of identifying patterns of behavior related to the use of the use oftechnology in financial institutions in different age groups. The research aims to to provide inspirationfor public projects and to contribute to the literature’s deeper understanding of the challengesunderstanding of the challenges highlighted, so it is hoped that it will reveal how the age of users andand ageism can influence their perception and use of the digital environments of financial institutions inthe financial institutions in the São Patrício Valley, Goiás. In addition, this analysis can help financialinstitutions institutions to understand how age impacts users’ behavior in relation to financial technology,allowing them to adjust their strategies and services to meet the specific needs of each generation.Specific needs of each generation.